Dynamics of Dimethyl Sulfoxide Penetration Into L929 Cells and L929-Based Spheroids - Moisieiev , Anton; Kovalenko, Igor; Kovalenko, Svitlana; Bozhok , Galyna; Gordienko , Olga (Problems of Cryobiology and Cryomedicine, 2021)
The study proposes an algorithm for calculating of appreciable permeability coefficients for multicellular structures in a cryoprotectant medium using physical and mathematical model of mass transfer. The values of surface-area-to-volume ratio for L929 cells at different temperatures were determined and the thermal expansion coefficient of the surface area of cell membranes was calculated (β = 2.7 × 10-3 /°C). The osmotically inactive volume for L929 cells and their spheroids was determined. Filtration and permeability coefficients to DMSO for L929 cells and in toto spheroids were found from the dynamic curves of relative volume change. The calculated parameters are the highest for individual cells and significantly (p <0.05) decrease for cells in the spheroids with increasing depth of their location, this reduction may be stipulated by a decrease in the available surface of cells in the spheroids for the penetration of extracellular substances. Obtained in this research permeability characteristics of spheroids can be used to develop optimal cryopreservation regimens for them. Probl Cryobiol Cryomed 2021; 31(4): 316–325